Two ways to success expansion of renewable energies in comparison between Germany's federal states. (August 2018) - Wurster, Stefan; Hagemann, Christian
Abstract: Expansion of renewable energies is a central pillar of the German energy transition towards a non-nuclear renewable system. The expansion rate is co-determined to a significant degree at the level of the federal states, and varies considerably from state to state. Apart from the existence of natural energy resources and general economic conditions, do parties in government play an important role for the development at the state level? We consider potentially influential factors in a fuzzy-set Qualitative Comparative Analysis (fsQCA) focusing on the expansion of renewable electricity production in all 16 federal German states from 2004 to 2014. As a result, two promising ways for accelerated expansion of renewable electricity production can be identified. On the one hand, a group of economically less developed states have succeeded in promoting expansion and uses it as part of an economic modernization strategy. Within the economically more developed states, however, the party-political composition of the state governments (Green party's involvement) plays a significant role. These results also have implications for other (federal) countries beyond Germany, pointing to tailor-made policy strategies that consider these specific circumstances. Highlights: Expansion of renewable electricity production varies from state to state in Germany. Two ways for accelerated expansion at the state level can be identified. Poor states can use it as part of an economic modernization strategy. In rich states, party government plays a significant role. Tailor made policy strategies must consider these specific circumstances.